Estimation of quantitative genetic parameters for dry matter yield and vegetative persistence-related traits in a white clover training population - Ehoche OG; Arojju SK; Cousins G; O'Connor JR; Maw B; Tate JA; Lockhart PJ; Jahufer MZZ; Griffiths AG (Wiley Periodicals LLC on behalf of Crop Science Society of America, 2022)
White clover (Trifolium repens L.), an economically important forage legume in temperate pastures, provides quality herbage and plant-available nitrogen. Enhancing breeding efforts to improve dry matter (DM) yield and vegetative persistence will increase on-farm value of this forage. To increase genetic gain for such traits, breeding tools like genomic selection have proven to be highly valuable in other crops. However, its success relies on a sufficiently large training population and key fundamentals of selective breeding, that is, presence of additive variation. We investigated quantitative genetic parameters for spring DM yield and vegetative persistence in a white clover training population comprising 200 half-sibling (HS) families. This population was established in a replicated cattle-grazed, mixed-sward field trial at two contrasting locations and assessed for spring DM yield and stolon-related vegetative persistence traits over a 3-yr period. The additive variation and genotype × environment interactions, comprising the effects from year, season, and location were significant (P <.05) for most traits. Narrow-sense heritability for all traits ranged from low (.13; post-summer stolon branches) to high (.73; leaf size) and there was a positive phenotypic correlation (.28) between spring DM yield and stolon number. These results indicate that both spring DM yield and persistence can be concurrently improved through selective breeding in the current population. We also demonstrated that applying a high selection pressure produces the highest predicted genetic gain. There is, however, a trade-off between genetic gain and diversity in the population for the long-term success of a breeding program.